De mãe substituta a babá malvada? : representações sociais sobre professora de bebês segundo acadêmicos de Pedagogia da UFMT, Campus Cuiabá - Ramos, Carla Adriana Rossi (2012)
This study presents the results of a research about the social representations (SR) of the academic Bachelor's Degree Pedagogy of the Federal University of Mato Grosso, Cuiabá campus about being teacher of babies. The theoretical approach adopted was the Theory of Social representations of Moscovici (1978, 2003) in conjunction with Theory Abric Central Nucleus (1998), as well as studies of Chombart Lauwe (1991), Aries (1981), Heywood (2004), Sarmento (2007), Haddad (2009), and Post Hohmann (2007), Cerise (2002), Morenttine (2000), Tardif (2005), Kuhlmann Jr. and Fernandes (2004), Del Priore (2008), Montenegro (2001), Dubar (2005) and others. The study analyzes evocations of 213 academics, collected through the technique of word association, from the motes inducing mother, nanny and induces the expression teacher of babies. The information collected was processed by the computer program Permetettant Ensemble Programmes l'Analyse (EVOC) and sub-Complex and Selevoc considering corporate on the average order (OME) and order of importance (IMO) and the evocations of intersection of the variable year. The program Cohesive Hierarchical implicative Classification (CHIC), by analyzing the possible classical implicative understanding of connections between words evoked. The program Analyse Lexical d'Contexte a pair of Esemble Segments of Text (Alceste) identified different classes of objects on the discursive representation of this study. The results concerning the representation of mother highlighted that there is a consensus among academics, love being identified as the organizing principle of representation. Other attributes such as dedication, responsibility, patience, affection and tenderness, conduct themselves as expected of a good mother. For scholars mother's love is understood as something natural. With regard to the motto inducer nanny, the data showed an anchored in the image representation of the second parent, whose activities are concentrated around the home environment. Observed results highlighted an estrangement from the motto teacher of babies. Attributes: Education, care and education contribute to the centrality of representation, the evocations training, mediator, educator, professional educator, aunt and babysitter, deployed in the area of contrast announce that contact with the universe provided by academic faculty may be contributing to a redefinition of the representation of professionals who work in nurseries, although the data show that there is a silence about the content associated with the educational nature of the teaching activities in the nursery, and indicates competing social roles, now anchored professional advertising content the image of the school, sometimes indicating sustained in social roles mothering practices. In general, the representation of a teacher of babies presents diffuse through three images: 1 - surrogate mother, 2 - teacher and 3 - babysitter, showing greater adherence to the former than the latter. The academic discourse of an explicit rejection of the nanny, characterized as that mishandling, although the meanings assigned to it closer to the meaning given to mothers. The data reveal the need for reflection on the role of teachers of infants, the educational character of the nurseries, the processes of development and learning of infants, the functions of institutions, as well as the conception of the child.